2019
DOI: 10.1101/2019.12.18.881680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Correlation of Serum BDNF and microRNA Content in Rats with Rapid or Late Onset of Heavy Alcohol Use

Abstract: Heavy alcohol use reduces the levels of the brain-derived neurotrophic factor (BDNF) in the prefrontal cortex of rodents through the upregulation of microRNAs targeting BDNF mRNA. In humans, an inverse correlation exists between circulating blood levels of BDNF and the severity of psychiatric disorders including alcohol abuse. Here, we set out to determine whether a history of heavy alcohol use produces comparable alterations in the blood of rats. We used an intermittent access to 20% alcohol using the 2-bottl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 85 publications
0
3
2
Order By: Relevance
“…The apparent contradiction between this later study and the present results (as well as the former study) may be due to differences in vendor (Harlan vs. Charles River) or laboratory, as the drinking levels in both sexes in the later study averaged around 5 g/kg/day, which is more similar to the male drinking levels in the present experiment (6.71 g/kg/day) and the former study. Of note, cluster analysis of the present results demonstrated that it was roughly half of the females, rather than all, that drank higher levels of EtOH than males, not unlike the different phenotypes of male intermittent‐access drinkers identified in earlier studies (Ehinger et al, 2021; Pandey & Barson, 2020). Examining weekly levels of intermittent access 20% EtOH drinking, different studies have reported different patterns.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The apparent contradiction between this later study and the present results (as well as the former study) may be due to differences in vendor (Harlan vs. Charles River) or laboratory, as the drinking levels in both sexes in the later study averaged around 5 g/kg/day, which is more similar to the male drinking levels in the present experiment (6.71 g/kg/day) and the former study. Of note, cluster analysis of the present results demonstrated that it was roughly half of the females, rather than all, that drank higher levels of EtOH than males, not unlike the different phenotypes of male intermittent‐access drinkers identified in earlier studies (Ehinger et al, 2021; Pandey & Barson, 2020). Examining weekly levels of intermittent access 20% EtOH drinking, different studies have reported different patterns.…”
Section: Discussioncontrasting
confidence: 51%
“…Charles River) or laboratory, as the drinking levels in both sexes in the later study averaged around 5 g/kg/day, which is more similar to the male drinking levels in the present experiment (6.71 g/kg/ day) and the former study. Of note, cluster analysis of the present results demonstrated that it was roughly half of the females, rather than all, that drank higher levels of EtOH than males, not unlike the different phenotypes of male intermittent-access drinkers identified in earlier studies (Ehinger et al, 2021;Pandey & Barson, 2020).…”
Section: F I G U R Econtrasting
confidence: 55%
“…The expression of striatal BDNF correlates with the expression of CREB, TrkB, and pri-miR-132 following amphetamine application in rats [236]. Heavy alcohol use causes upregulation of some miRNAs and consequently regulates BDNF values [237]. Adolescent intermittent ethanol exposure increased the miR-137 expression level in the amygdala.…”
Section: Substance Use Disordersmentioning
confidence: 99%
“…Specifically, we found that activation of BDNF signaling in the dorsolateral striatum (DLS), which is mediated via the receptor tyrosine kinase, tropomyosin-related kinase B (TrkB), keeps alcohol intake in moderation [10-13]. We further showed that escalation of drinking occurs when this protective signaling pathway ceases to function [14-17].…”
Section: Introductionmentioning
confidence: 99%